Therapeutic approaches for chronic hepatitis C: a concise review - Nawaz, Allah; Manzoor, Azhar; Ahmed, Saeed; Ahmed, Naveed; Abbas, Waseem; Mir, Mushtaq Ahmad; Bilal, Muhammad; Sheikh, Alisha; Ahmad, Saleem; Jeelani, Ishtiaq; Nakagawa, Takashi (Frontiers in Pharmacology, 2024)
Hepatitis C virus (HCV) infection is a significant global health concern, prompting the need for effective treatment strategies. This in-depth review critically assesses the landscape of HCV treatment, drawing parallels between traditional interferon/ribavirin therapy historically pivotal in HCV management and herbal approaches rooted in traditional and complementary medicine. Advancements in therapeutic development and enhanced clinical outcomes axis on a comprehensive understanding of the diverse HCV genome, its natural variations, pathogenesis, and the impact of dietary, social, environmental, and economic factors. A thorough analysis was conducted through reputable sources such as Science Direct, PubMed, Scopus, Web of Science, books, and dissertations. This review primarily focuses on the intricate nature of HCV genomes and explores the potential of botanical drugs in both preventing and treating HCV infections.